2018
DOI: 10.1155/2018/7515767
|View full text |Cite
|
Sign up to set email alerts
|

Potential Crosstalk between Fructose and Melatonin: A New Role of Melatonin—Inhibiting the Metabolic Effects of Fructose

Abstract: Increased consumption of energy-dense foods such as fructose-rich syrups represents one of the significant, growing concerns related to the alarming trend of overweight, obesity, and metabolic disorders worldwide. Metabolic pathways affected by fructose involve genes related to lipogenesis/lipolysis, beta-oxidation, mitochondrial biogenesis, gluconeogenesis, oxidative phosphorylation pathways, or altering of circadian production of insulin and leptin. Moreover, fructose can be a risk factor during pregnancy el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 85 publications
(150 reference statements)
0
7
0
Order By: Relevance
“…It is believed that excess doses of melatonin can worsen sleep cycles, with best effects reported to be at 0.3 to 0.5 mg. 57 Oral pills are the most commonly used; however, sublingual tablets have more consistent and overall increased bioavailability 58 because they are not subject to the first-pass effect. 59 Melatonin has been shown to inhibit the harmful effects of fructose on clock genes and protect against reactive oxygen species. 60 Melatonin has also been shown to regulate leptin and adiponectin secretion cycles, further underlying the reciprocal relationship of these hormonal cascades.…”
Section: Melatoninmentioning
confidence: 99%
“…It is believed that excess doses of melatonin can worsen sleep cycles, with best effects reported to be at 0.3 to 0.5 mg. 57 Oral pills are the most commonly used; however, sublingual tablets have more consistent and overall increased bioavailability 58 because they are not subject to the first-pass effect. 59 Melatonin has been shown to inhibit the harmful effects of fructose on clock genes and protect against reactive oxygen species. 60 Melatonin has also been shown to regulate leptin and adiponectin secretion cycles, further underlying the reciprocal relationship of these hormonal cascades.…”
Section: Melatoninmentioning
confidence: 99%
“…Many studies indicated that melatonin (N-acetyl-5-methoxytryptamine), the nighttime indole produced by pineal and many extra-pineal tissues, is effective against the metabolic syndrome [33,34,35]. Recently, melatonin reverses harmful effect of dietary fructose in animal models modulating metabolic pathways like lipogenesis and lipolysis, beta-oxidation, gluconeogenesis [36]. Lipophilic melatonin freely passes through all biological membranes and accumulates mainly into mitochondria where influences mitochondrial structure and function via PGC1 alpha signal [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have proven that nocturnal indole‐melatonin secreted by the pineal gland is effective in treating metabolic syndrome 43 . More recently, melatonin has been found to reverse the adverse effects of a high‐glycemic diet and regulate metabolic pathways, such as gluconeogenesis, β‐oxidation, lipid production, and decomposition 44 . Melatonin may also be taken up in the liver through specific cellular and nuclear receptors 45 .…”
Section: Discussionmentioning
confidence: 99%